Environment Matters at the World Bank : Annual Review 2003 - World Bank (Washington, DC, 2013)
This issue, which serves as the annual review on the environment, looks at the Bank's work from July 2002 through June 2003, dedicated this year to Water and the Environment, on the occasion of the Fifth World Parks Congress in Durban, South Africa. Following the overview, which reviews progress in the implementation of the Environment strategy, the report presents viewpoints on ways to move forward in delivering water as committed in South Africa, but also reflecting on the need for a more integrated approach to water resources management. Various other articles feature the Bank's new water resources strategy, and environmental flows, that is, from linking catchments to coasts in water resources management, to protected areas as tools for water conservation, and management. Regional articles describe progress in implementing the environment strategy, and supporting client's efforts in promoting appropriate environmental policies, and programs. Highlights from the International Finance Corporation (IFC) scan efforts to promote private sector investment in water supply and sanitation, and environmental improvements, while efforts by the World Bank Institute (WBI) inform on training and learning activities that sponsor policy, and knowledge-sharing as it relates to the environment.